Jury Must Die - O'Connell, Carol (London : Arrow, 2004)
After bringing in a unanimous and very dubious acquittal in a murder case, only three of the original jurors remain alive. And someone, known only as the 'Reaper' because of the signature of a bloody scythe left on the crime scenes, is clearly determined to make a clean sweep of the terrified survivors. Detective Sgt. Riker, although on paid sick leave after a teenage psycopath pumped four bullets into his chest, has taken a keen but unofficial interest in the case. And his NYPD Special Crimes partner, Kathy Mallory, orphan, sociapath and computer genius, is resolute that there will be no more personal defects in her life, and determined to discover the identity of the killer before he, or she makes a complete mockery of justice.
Originally published: London: Hutchinson, 2003.
Keywords: Policewomen -- New York (State) -- New York; Detective and mystery stories